Pengaruh Pertumbuhan Investasi Asing terhadap Industri Hiburan Malam di Kota Batam (2008-2012) - Syarifah Shahnaz Alatas; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research is about how the impact of globalization in a Semi Phery-Phery State. The problems taken by the writer is trying to find the links and impacts happening of foreign investment with night club industries in Batam City.This research uses Paul R. Viotti and Mark V. Kauppi's Theory, which the distribution of power and profits, The Semi Phery-Phery States get profits less than The Core States. As a result of the dependency relationship then emerging national policy influenced the political power of the capitalist. In addition, this study also uses Marjorie Ferguson's Theory, which essentially has turned globalization into in asset that caused change or loss local identity. The most sources of data collection on this research is qualitative research methods with using the library research technique, observation and interview.This research shows the impact of capitalism , specifically relationship between foreign investment that supports the globalization of western culture in the city of Batam . The habits of the expatriates and tourists in Batam make night club industries grow fast, and the influence has received support from local residents that prostitution can not be avoided .Keywords :The Ethics of Expatriate and Tourism Development: Geographies Strategic , Mobility, Night club and Prostitution